Formulasi body scrub dari kombinasi temu putih (Curcuma zedoaria) dan biji kurma (Phoenix dactylifera) - Yuliawati, Yuliawati; Elisma, Elisma; Utami, Diah Tri; Pratiwi, Puspa Dwi (Journal of Pharmaceutical and Sciences, 2023)
Body scrub is a cosmetic form that removes dead skin cells caused by free radicals from various pollutants and ultraviolet (UV) radiation so skin cells become more accessible to regenerate. White turmeric (Curcuma zedoaria) and date seeds (Phoenix dactylifera) are plants that contain bioactive compounds to maintain and nourish the skin and have antioxidant activity. Besides, date seeds also have the potential as exfoliating agents to facilitate the release of dead skin cells. This study aimed to formulate a body scrub containing ethanol extract of white turmeric rhizome and date seed powder with five types of formulas (K+, K-, F1, F2, F3). This type of research is a true experimental, which includes the formulation and stability test. The stability test was conducted with the Cycling test method in 6 cycles (1 cycle for 2x24 hours) at temperatures of -4oC and 40oC and four months for stability at room temperature. Parameters observed include organolepticity, homogeneity, dispersibility, adhesion, pH, and viscosity. The results showed that this body scrub did not show any change in the organoleptic character, homogeneity, spreadability, adhesion, or pH values that met the requirements of a body scrub preparation. Viscosity met the requirement for stability test for room temperature in four months. This study concludes that the combination of ethanol extract of white turmeric rhizome and date seed powder seeds can be formulated to be a body scrub dosage form.